Parallel algorithms and architecture for computation of manipulator forward dynamics - Fijany, A.; Bejczy, A.K. (Proceedings. 1991 IEEE International Conference on Robotics and Automation, 1991)
Parallel computation of manipulator forward dynamics is investigated. Considering the three classes of algorithms for the problem, the authors show that the O(n/sup 3/) algorithms are the most efficient for parallel computation. Parallel algorithms for computation of inertia matrix, the bias vector, and the linear system solution are developed which can be efficiently implemented on a unique architecture, a triangular array of n(n+1)/2 processors with a nearest neighbor interconnection. This architecture is highly suitable for VLSI and WSI implementation.< >